Associations of CYP2C9 and CYP2A6 Polymorphisms with the Concentrations of Valproate and its Hepatotoxin Metabolites and Valproate‐Induced Hepatotoxicity. Issue 2 (3rd May 2017) - Zhao, Mingming; Zhang, Ti; Li, Guofei; Qiu, Feng; Sun, Yaxin; Zhao, Limei
Abstract: The aim of this study was to compare genetic polymorphisms and concentrations of hepatotoxic metabolites in patients with epilepsy and liver injury and those with normal liver function receiving valproate monotherapy to identify risk factors for VPA‐induced hepatotoxicity. A total of 279 Chinese patients with epilepsy were divided into an abnormal liver function (ANLFT) group (n = 79) and a normal liver function (NLFT) group (n = 200). Polymerase chain reaction–restriction fragment length polymorphism PCR‐RFLP and nested PCR were applied to identify the frequency of two SNPs in candidate genes. Serum concentrations of VPA and its major metabolites were determined by Ultra‐Performance Liquid Chromatography–tandem mass spectrometry UPLC‐MS/MS. Significant differences were found in genotype distributions of CYP2A6 and CYP2C9 between the two groups. The values of 4‐ene‐VPA and 2, 4‐diene‐VPA in the ANLFT group were significantly higher than in the NLFT group. Only CYP2A6 polymorphisms had associations with the concentrations of 4‐ene‐VPA and 2, 4‐diene‐VPA. CYP2A6*1/*4 and CYP2A6*4/*4 variant carriers had higher CDR4‐ene‐ VPA and CDR2, 4‐diene‐ VPA values than CYP2A6*1/*1 carriers. The logistic regression analysis showed that CYP2C9 and CYP2A6 were significant risk factors for hepatotoxicity by increasing the risk by 7.50 and 5.13 times, respectively. These findings provide preliminary evidence that CYP2A6 and CYP2C9 are associated with hepatotoxicity. However, only the CYP2A6 polymorphism was found to be associated with concentrations of 4‐ene‐VPA and 2, 4‐diene‐VPA. Potential important risk factors include mutated genotypes of CYP2C9 and CYP2A6 and higher concentrations of VPA, 4‐ene‐VPA and 2, 4‐diene‐VPA.